👤

3. (0-3p) Opuść nawiasy, zapisz wyrażenie w najprostszej postaci, a następnie oblicz jego
wartośa dla x =
1/2oraz y = - 5
(-2x-3y+6)-(4x-3y+12)​


Odpowiedź :

(-2x - 3y + 6) - (4x - 3y + 12) =

-2x - 3y + 6 - 4x - 3y + 12 =

-6x - 6y + 18 =

-6 × ½ - 6 × (-5) + 18 =

-1 + 30 + 18 =

47

Myślę że dobrze :'>

Odpowiedź:

3. (0-3p) Opuść nawiasy, zapisz wyrażenie w najprostszej postaci, a następnie oblicz jego

wartośa dla x =

1/2oraz y = - 5

(-2x-3y+6)-(4x-3y+12)​ = -2x - 3y + 6 - 4x + 3y - 12 = -6x - 6 = -6 * 1/2 - 6 = -3 - 6 = -9

x = 1/2

y = -5

Szczegółowe wyjaśnienie: